X-band Doppler simulator for sport projectile radars - Barsch, Binjamin (Department of Electrical Engineering, 2018)
Systems engineering has always required that hardware is evaluated in its desired environment. However, this may not be feasible as the target or environment may be too complex or too costly to use at any given time. This is a common problem with evaluating Doppler radars as well, since the inherent property of a Doppler radar is to measure the radial velocity of objects in motion like aircraft or projectiles. A common solution to this problem is to perform a hardware- in-the-loop (HIL) simulation. This usually comprises of a device that does a real-time simulation of the environment or moving target. In the field of RF engineering, such a device is known as a repeater or a Doppler simulator. Depending on the application, these devices use either the digital radio frequency memory (DRFM) or direct digital synthesis (DDS) simulation method. Developing Doppler simulators as a diagnostic tool for sport Doppler radars is a growing need to evaluate and assess the performance of these radars. This dissertation will investigate the design and development of a Doppler simulator that can be used to simulate projectiles for sport Doppler radars. The scope of this dissertation was restricted to the sport of golf using continuous wave (CW) X-band Doppler radars. Raw data was measured by a Doppler radar to determine the velocity profiles of golf balls in flight. From these profiles, flight models were developed that could be simulated using a Doppler simulator. An Arduino Due microcontroller was used to implement the digital DDS method and to simulate these velocity profiles. This microcontroller was integrated into an existing Doppler simulator that lacked the capabilities to simulate a velocity profile. Results showed that the projectile based sport Doppler simulator was effective in simulating the modeled flight trajectories. A close comparison between the simulated and measured result were shown. For three different types of golf shots, the average error between the simulated and measured trajectories was -0.169 m/s while the standard deviation was 0.28 m/s. This dissertation also showed future possibilities in simulating a diverse range of projectiles and targets.